Pleth Variability Index Guided Volume Optimisation in Major Gynaecologic Surgery - SARAÇOĞLU, AYTEN (My University, 2022)
Objective: To compare conventional fluid management (CFM) with pleth variability index (PVI) guided goal-directed fluid management (GDFM) during elective total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAH+BSO) operations. Study Design: Randomised controlled trial. Place and Duration of Study: Department of Anaesthesiology and Reanimation, Faculty of Medicine, Health Sciences University, Kartal Dr. Lutfi Kirdar City Hospital, Istanbul, Turkey, from February to July 2021. Methodology: This trial included 78 patients aged 18-65 years with ASA I-III who would undergo elective TAH-BSO under general anaesthesia. Following randomisation with the closed envelope method, standard monitoring, and 250 ml crystalloid infusion during anaesthesia induction, maintenance fluid therapy was administered at 8-10 ml/Kg/hour to the control group and 2-3 ml/Kg/hour to the PVI group. If the mean arterial pressure (MAP) was ≤65 mmHg and/or the MAP was decreased by more than 20%, and the PVI was >13%, a 250 ml colloid bolus was given. When there was no response, a vasoactive agent was administered. Vital signs, laboratory findings, and postoperative complications were evaluated. Results: Age, weight, BMI, urine output, bleeding, hospital stay, comorbidities, intraoperative use of blood products, and complication rates were not significantly different between the PVI and CFM groups (p>0.05). The PVI group had shorter operational times and used less crystalloid than the control group (p=0.033 and p<0.001, respectively). The PVI group's postoperative base excess (BE) levels changed significantly less than the control group's (p<0.001). In both pre- and postoperative haemoglobin, haematocrit, urea, creatinine, electrolytes, and lactate measurements, there were no statistically significant differences between the groups (p>0.05). Conclusion: PVI-GDFM is equally safe as CFM for intraoperative fluid management during elective complete abdominal hysterectomy and bilateral salpingo-oophorectomy procedures.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & İÇECEK; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Pleth variability index; Fluid management; Base excess